Near-orthogonal overlay communications in LoS channel enabled by novel OAM beams without central energy voids: an experimental study - Zhao, Yufei (2024)
This paper introduces a novel Line-of-Sight (LoS) Multiple-Input Multiple-Output (MIMO) communication architecture leveraging non-traditional Orbital Angular Momentum (OAM) beams. Challenging the conventional paradigm of hollow-emitting OAM beams, this study presents an innovative OAM generator that produces directional OAM beams without central energy voids, aligning their radiation patterns with those of conventional planar wave horn antennas. Within the main lobe of radiation patterns, the phase variation characteristics inherent to OAM beams are ingeniously maintained, linking different OAM modes to the linear wavefront variation gradients, thereby reducing channel correlation in LoS scenarios and significantly augmenting the channel capacity of LoS-MIMO frameworks. Empirical validations conducted through a meticulously designed LoS-MIMO experimental platform reveal significant improvements in channel correlation coefficients, communication stability, and Bit Error Rate (BER) compared to systems utilizing traditional planar wave antennas. The experiment results underscore the potential of the novel OAM-based system to improve current LoS-MIMO communication protocols, and offer both academic and engineering guidance for the construction of practical communication infrastructures. Beyond its immediate contributions, this paper underscores a pivotal shift in the field of communications, pointing out that traditional communication algorithms have primarily focused on baseband signal processing while often overlooking the electromagnetic characteristics of the physical world. This research highlights that, in addition to radiation patterns, the wavefront phase variations of traditional antennas represent a new degree-of-freedom that can be exploited. Consequently, future communication algorithms designed around reconfigurable electromagnetic wavefront properties hold the promise of ushering wireless communications into a new era.